Merging Competencies, Valuing Diversity: The Multicultural Enterprise as an Emerging Model - Alessandro Arrighetti; Andrea Lasagni; Daniela Gnarini; Renata Semenza (International Organization for Migration (IOM), 2020)
Multicultural enterprises can be considered as a subset of the complex phenomenon of migrant entrepreneurship Starting from a theoretical overview of the phenomenon, the study analyzes multicultural enterprise experiences. Various topics, ranging from perceived advantages to obstacles encountered in everyday business, are discussed. In its conclusion, the study presents recommendations on how to adjust support actions to the specific needs of multicultural enterprises.
Keywords: L20; 330; Multicultural Firm; Migrant Firm